Mechanobiology in cardiology: Micro‐ and nanotechnologies to probe mechanosignaling. Issue 2 (12th January 2021) - Yadav, Sharda; Ta, Hang T.; Nguyen, Nam‐Trung
Abstract: The past few decades have shown significant growth in the study of mechanical effects on cellular properties. Novel methods and techniques had been developed to analyze the changes in the biophysical and biomechanical properties of cells. Recently, it has been reported that interaction between the external environment and cardiomyocytes would be essential for the function of the heart due to the importance of mechanical signaling. Physical forces play a major role in the development of cardiovascular disease. In this mini review, we discuss recent advances in technology for probing mechanobiology signals from the cardiac tissue and focus on the unmet needs and challenges to completely understand the mechanobiology of cardiac tissues. Abstract : This mini review elucidates the recent advances in technology for probing mechanobiology signals from the cardiac tissue. It also focuses on the unmet needs and challenges to completely understand the mechanobiology of cardiac tissues.